INTERPRETATION OF CASUAL CONVERSATION ANALYSIS - Riski Safitri; Efendi Efendi; Titik Hardewi Yani; Dino Adi Putra; Veni Veni; Yanti Nazmai Ekaputri (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2023)
Casual conversation is a critical site for the social construction of reality. The relaxed nature of casual conversation leads to a very common perception by those who participate in such talk that it is trivial and that nothing happens. Conversation Analysis (CA) is one of the approaches in discourse which has its roots in the field of ethnomethodology, one of the branches in sociology. The purpose of this research is to analyze the casual conversation between two close friends. The duration of the conversation is about 10 minutes long. The setting of the conversation is in the area of campus. In this paper, the casual conversation is analyzed from the form of negotiation, the turn taking, the linguistic competence and the strategic competence.